(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The uropathogenicEscherichia coli (UPEC)are causative agents of urinary tract infection (UTI) throughout the world. This study aimed at analyzing the prevalence of UTI among different age and gender in Chittagong, the second most popular city of Bangladesh. We performed a PCR based UPEC detection method by using 16S rRNA and phylotyping by multiplex PCR.We found E.coli in 83.43% of UTI samples in this study. Among these, 42% of UPEC belongs to B2 phylogroup along with A,B1,C,D,E and F.Moreover, there was a significant association of UPEC infection with age and gender. To be more specific, 45.03% of males and 54.97% of females UTI patients were infected with UPEC.Therefore,we believe that this study would play a crucial role in detecting and managing UPEC induced UTI by understanding the prevalence of UPEC and their phylotype in the Chittagong region of Bangladesh. The Chittagong Univ. J. B. Sci. 9(1&2):29-38, 2019